La participation composante du développement durable : quatre études de cas - Marc Mormont; Catherine Mougenot; Christine Dasnoy (VertigO)
Based on various case studies, this paper analyses public participation as a circulation process : collective action circulates controversial questions between various cognitive and normative spheres (local / global, policy / science). These moves allow to reorganise knowledges and to reformulate norms. Its efficiency depends on its capacity to constitute new collectives of environmental management. This perspective calls on an experimentalist mode of public policy.